Effect of low dose intracoronary alteplase on global circumferential strain (myocardial strain CMR substudy from the T-TIME trial). (14th October 2021) - McCartney, P; Ang, D; Mangion, K; McEntegart, M; Greenwood, J P; Muir, D; Chowdhary, S; Appleby, C; Cotton, J M; Eteiba, H; Oldroyd, K G; Maznyczka, A; et al.
Abstract: Background: Microvascular obstruction affects half of patients with ST-segment elevation myocardial infarction (STEMI) and confers an adverse prognosis. Feature-tracking (FT) cardiac magnetic resonance (CMR) allows myocardial strain assessment from standard cine images without the need for specialist sequences. Myocardial strain reflects both systolic and diastolic function allowing the assessment of both global and regional myocardial deformation. Strain recovery is impaired in patients with microvascular obstruction. There is growing evidence to suggest that global circumferential strain may offer incremental value beyond traditional CMR endpoints. Purpose: We aimed to determine whether a therapeutic strategy involving low-dose intracoronary alteplase improves global circumferential strain in STEMI. Methods: Between March 17, 2016, and December 21, 2017, 440 patients presenting at 11 hospitals in the United Kingdom within 6 hours of STEMI were randomised in a 1:1:1 dose-ranging trial design. Participants were randomly assigned to treatment with placebo (n=151), alteplase 10mg (n=144), or alteplase 20mg (n=145). The primary outcome was the amount of microvascular obstruction (%left ventricular mass) quantified by CMR at 2–7 days. Global circumferential strain was a prespecified secondary endpoint measured at 2–7 days and 3 months. Troponin T AUC was measured at 0, 2, and 24 hours post reperfusion. Patients were followed up to 1 year with all events adjudicated by an independent committee. Results: Among the 440 patients who were randomised (mean age 60.5 years; 85% male), the primary endpoint was achieved in 396 (90%), all patients were followed up to 1 year for clinical events. The amount (mean, standard deviation) of microvascular obstruction was not different between the groups (2.3% vs. 2.6% vs. 3.5% left ventricular mass); p=0.28. Global circumferential strain was worse in patients receiving alteplase. −23.1% (placebo) vs −20.6 (10mg alteplase) vs −22.0% (20mg alteplase); mean difference for both doses combined vs placebo: 1.8% (95% CI 0.5, 3.2), p=0.009. There were no differences between groups in the other CMR endpoints including LV ejection fraction (LVEF). The area-under-the-curve for troponin T measured in 317 (72%) patients was increased in both treatment groups compared to placebo, mean difference 1.53 (95% CI: 1.16, 2.01), p=0.002. There were no differences in MACE at 1 year; placebo n=16 (10.6%), 10mg alteplase n=22 (15.3%), 20mg alteplase group n=15 (10.3%). Conclusion: In patients presenting within 6 hours of STEMI, low-dose intracoronary alteplase compared with placebo did not reduce microvascular obstruction. There was a reduction in global circumferential strain and an increase in Troponin T AUC supporting an increase in myocardial injury early after reperfusion in patients receiving alteplase. There was no differences in MACE at one year suggesting no long-term clinical sequelae. FUNDunding Acknowledgement: Type of funding sources: Other. Main funding source(s): T-TIME was supported by grant 12/170/4 from the Efficacy and Mechanism Evaluation (EME) programme of the National Institute for Health Research (NIHR-EME). Boehringer-Ingelheim U.K. Ltd. provided the study drugs (alteplase 10mg, 20mg), matched placebo, and sterile water for injection.